Molecular Characterization of Patients with Cryptorchidism: Preliminary Search for an Expression Profile Related to That of Testicular Germ-Cell Tumors - Fabiola García-Andrade; Rosa María Vigueras-Villaseñor; Margarita Dolores Chávez-Saldaña; Julio César Rojas-Castañeda; Ivan Uriel Bahena-Ocampo; Elena Aréchaga-Ocampo; Mauricio Flores-Fortis; José Díaz-Chávez; Luis Alonso Herrera; Daniel Adrian Landero-Huerta (Diagnostics, 2023)
Cryptorchidism (CO) is a risk factor for the development of testicular germ-cell tumors (TGCT). This is supported by reports showing the persistence of gonocytes in CO patients. These cells are proposed to be related to the development of germ-cell neoplasia in situ (GCNIS), which is considered the precursor stage/lesion of TGCT. Therefore, it is proposed that some patients with CO could express some molecular markers related to TGCT. In this study, we analyzed testicular tissue samples from CO, TGCT, and controls. We determined the expression of POU5F1, PLAP, and KIT by immunohistochemistry and that of the hsa-miR-371-373 cluster, hsa-miR-367, and LATS2, PTEN, and IGFR1 genes by RT-qPCR. We then carried out a bioinformatic analysis to identify other possible candidate genes as tumor biomarkers. We found that 16.7% (2/12) of the CO patients presented increased expression of POU5F1, KIT, PLAP, hsa-miR-371-373, and hsa-miR-367 and decreased expression of LATS2 and IGF1R. Finally, the genes ARID4B, GALNT3, and KPNA6 were identified as other possible candidate tumor biomarkers. This is the first report describing the expression of the hsa-miR-371-373 cluster, hsa-miR-367, LATS2, and IGF1R in the testicular tissues of two CO patients with cells immune-positive to POU5F1, PLAP, and KIT, which is similar to what is observed in TGCT.